Research on the effect of pull marketing from the perspective of Social responsibility - Zhang, Shuoqi (Economics & Management Review, 2022)
In the post-epidemic era, with economic recovery and prosperity, how to market and establish a foothold in the market for fast retailing brands represented by instant noodles has become a long-term problem to be considered. Laotan brand in health problems, reputation declined sharply; The White Elephant brand focuses on the marketing of health and safety and social welfare, and the sales have been successful. In view of this phenomenon, the purpose of this study is to analyze the conditions for the successful marketing of White Elephant brand, and try to explore the role of social publicity in it.